Including Faith Communities in Disaster Recovery Phase via Religious Diversity: Qualitative Descriptive Analysis - Ha, Kyoo-Man (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
A hypothesis on the relationship between disaster management and religion is that the benefits of disaster recovery increase with an increase in religious diversity in disaster recovery. This article aims to examine the role of faith communities during disaster recovery with the ultimate goal of increasing religious diversity. Qualitative descriptive analysis was used to examine mass care–oriented disaster recovery and further specialized care across four stakeholders: religiously highly diverse countries, religiously moderately diverse countries, religiously least diverse countries, and international organizations. Additionally, the PRISMA 2020 checklist and flow diagram were employed as supplementary tools. A key tenet was that all four stakeholders should try to supplement mass care–oriented disaster recovery (e.g., sheltering, feeding, health services) with further specialized care while appropriately addressing religious tolerance, literacy, and competency, as well as the roles of emergency managers and sustainable education. This study provided a more comprehensive description of including faith communities in disaster recovery than was available in the existing literature.